2012
DOI: 10.1021/es300447t
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Particulate and NOx Emissions by Diesel Engine Parameter Adjustments with HVO Fuel

Abstract: Hydrotreated vegetable oil (HVO) diesel fuel is a promising biofuel candidate that can complement or substitute traditional diesel fuel in engines. It has been already reported that by changing the fuel from conventional EN590 diesel to HVO decreases exhaust emissions. However, as the fuels have certain chemical and physical differences, it is clear that the full advantage of HVO cannot be realized unless the engine is optimized for the new fuel. In this article, we studied how much exhaust emissions can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…[26,2830] However, the majority of those studies reported effects of the NO X emissions, but none reported separately the effects on two major NO X components: NO and NO 2 . Due to the relatively high toxicity [34] and technical and economic issues related to ventilation, the NO 2 emissions are of particular concern in the case of confined occupational environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[26,2830] However, the majority of those studies reported effects of the NO X emissions, but none reported separately the effects on two major NO X components: NO and NO 2 . Due to the relatively high toxicity [34] and technical and economic issues related to ventilation, the NO 2 emissions are of particular concern in the case of confined occupational environments.…”
Section: Discussionmentioning
confidence: 99%
“…Those engines were not adjusted to compensate for the substantial differences in physical and chemical properties between test fuels. Independent studies [26,30] have shown that engines with modifications made to compensate for changes in fuel properties, such as increasing injection pressure, theoretically, have the potential for relatively minor additional reductions in DPM emissions on top of those achieved by using HVORD in place of ULSD. The practices with FAME biodiesel fuels showed that mine operators in the U.S. are unlikely to invest into optimization of in-use engines to specific fuels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HVORD is favored over FAME biodiesel due to lower environmental impact (Yano et al, 2015). Compared with ULSD, HVORD has favorable effects not only on particulate, carbon monoxide and total hydrocarbon emissions but also NO X emissions (Aatola et al, 2008; Happonen et al, 2012; Kim et al, 2014; Westphal et al, 2013; Bugarski et al, 2015). Westphal et al (2013) found that HVORD particulate extracts have lower mutagenicity than ULSD and rape-seed and jatropha FAME biodiesel particulate extracts.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that NO x emission reduced by 25-45% depending on load and on the IVC timing of the Miller cycle, but filter smoke number (FSN) increased simultaneously. Happonen et al (2012) studied the effect of advanced intake valve closing and fuel injection timings on exhaust emissions with an engine run with HVO fuel. They obtained notable reductions with all tested loads in PM and NO x emissions by combining advanced intake valve closing and fuel injection timings with EGR.…”
Section: Introductionmentioning
confidence: 99%